Toward a better understanding of gastrointestinal nitrergic neuromuscular transmission. Issue 7 (14th May 2014) - Lies, B.; Groneberg, D.; Friebe, A.
Abstract Background Nitric oxide (NO) is an important inhibitory neurotransmitter in the gastrointestinal (GI) tract. The majority of nitrergic effects are transduced by NO‐sensitive guanylyl cyclase (NO‐GC) as the receptor for NO, and, thus, mediated by cGMP‐dependent mechanisms. Work carried out during the past years has demonstrated NO to be largely involved in GI smooth muscle relaxation and motility. However, detailed investigation of nitrergic signaling has turned out to be complicated as NO‐GC was identified in several different GI cell types such as smooth muscle cells, interstitial cells of Cajal and fibroblast‐like cells. With regards to nitrergic neurotransmission, special focus has been placed on the role of interstitial cells of Cajal using mutant mice with reduced populations of ICC. Recently, global and cell‐specific knockout mice for enzymes participating in nitrergic signaling have been generated providing a suitable approach to further examine the role of NO‐mediated signaling in GI smooth muscle. Purpose This review discusses the current knowledge on nitrergic mechanisms in gastrointestinal neuromuscular transmission with a focus on genetic models and outlines possible further investigations to gain better understanding on NO‐mediated effects in the GI tract.